Algorithm for carrying out a procedure for verification of a spectrophotometric method for analysis of solid-dosed dosage forms according to the requirements of SPHU 2.0 - Bevz, Nataliia; Georgiyants, Victoria; Gryzodub, Oleksandr (ScienceRise: Pharmaceutical Science, 2019)
Aim. The increase in the pharmaceutical market of Ukraine of the range of medicines leads to stricter requirements for their quality. According to the requirements of international standards ISO, ICH, GMP, current legislation of Ukraine and the State Pharmacopoeia of Ukraine, generic drugs must be equivalent, and the analytical methods used for quality control, validated or verified. One of the available methods of analysis used both in pharmacy conditions and in quality control laboratories at enterprises and in independent control and analytical laboratories is absorption spectrophotometry in the ultraviolet and visible areas. Materials and methods. The method of absorption spectrophotometry in the ultraviolet and visible areas is used to quantify the active pharmaceutical ingredients in finished tablet dosage forms when the quantitative determination performed and when conducting pharmaco-technological tests, such as "Dissolution" and Uniformity of dosage units". Results. To use the method of absorption spectrophotometry for the quantitative evaluation of active pharmaceutical ingredients in finished drugs, it is necessary to verify the proposed methods and examine such validation characteristics as specificity, linearity, accuracy and precision of the proposed methods. At the same time, the uncertainty of the results of the analysis DAs, expressed as a one-sided confidence interval for the probability of 95 %, and which consists of the uncertainty of sample preparation (DSp) and the uncertainty of the final analytical operation (DFAO), must not exceed the maximum permissible total uncertainty of the analysis (maxDAs). Conclusions. The approaches of the State Pharmacopoeia of Ukraine to the methods for determining the quantitative content of active ingredients in tablets during the tests "Quantitative determination", "Dissolution", Uniformity of dosage units" were studied. The procedure has been proposed for verifying methods for quantitative determination of manufactured drugs using absorption spectrophotometry according to the requirements of the 2nd edition of the State Pharmacopoeia of Ukraine